"Stop talking around projects and talk about solutions": Positioning health within infrastructure policy to achieve the sustainable development goals. Issue 6 (June 2020) - Harris, Patrick; Riley, Emily; Dawson, Angus; Friel, Sharon; Lawson, Kenny
Highlights: We analyse infrastructure policy and public health intersections to meet the SDGs. Infrastructure (SDG 9) plays a society shaping role synergistic with a public health agenda (SDG 3). Political power causes 'project fever'; costly projects often detrimental to the public interest. Public health is novel for and insufficiently considered in infrastructure policy. Health and well-being focussed infrastructure policy will improve decisions in the public interest. Abstract: Purpose and setting: Infrastructure is a global multi-trillion dollar market presenting many opportunities and risks for sustainable development. This article aims to foster better conceptualisation of the connections and tensions between infrastructure policy and public health in the light of the Sustainable Development Goals, especially 'good health and wellbeing' (number 3) and 'industry, innovation and infrastructure' (number 9), based on findings from interviews with a purposive sample of senior practicing Australian infrastructure policy makers. Principal findings: We use an institutional framework to explore the ideas, actors, rules and mandates, and procedures underpinning the inclusion of health in infrastructure policy. Informants defined infrastructure as the construction and provision of services that facilitate economic, environmental and social outcomes. The tendency to default to infrastructure as essential for economic success has fundamental challenges for the SDGs, particularly the politically driven pursuit of 'mega-project' legacies, sector-specific siloed governance arrangements, and inadequate conceptualisations of costs and benefits. Conclusions: Public health and infrastructure policy are mutually re-enforcing given they both concern the public interest with implications for all 17 SDGs. Positioning health and wellbeing as fundamental societal outcomes from infrastructure decisions would go a long way to helping achieve the SDGs.